WASAṬIYYA AND THE URBAN MUSLIM MINORITY STATE: THE NCMF AND THE INSTITUTIONALIZATION OF ISLAMIC MODERATION IN THE PHILIPPINES - Bin Usman Imam, Luqman; Latif, Abdul; D. Madale, Aida (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
This paper argues that the National Commission on Muslim Filipinos (NCMF) plays a vital role in facilitating the inclusion and participation of marginalized Muslim minorities into the Philippine nation-state's development framework. While there have been extensive studies on how Wasaṭiyya was adopted by some Southeast Asian countries, little is known about this principle in the Philippines and how the government can utilize its state institutions like NCMF to address inclusion and welfare of its Muslim minority population. This study asks: How does the NCMF embodies and implements Wasaṭiyya principles in its mandates and programs for Muslim Filipinos? Specifically, through its diverse government programs and activities across key domains, NCMF substantively actualizes the principles of Wasaṭiyya - the Islamic values of moderation, justice, balance, ease, striving for excellence, and public good. The NCMF was chosen as the focus due to its unique position as the primary state body for Muslim affairs, offering a contemporary lens on minority governance. Thereby, it translates the abstract philosophical virtues into practical accommodation policies and arrangements that oblige the state's commitments and responsibilities towards respecting and upholding the identity, rights, welfare, and dignity of Muslim Filipinos. Furthermore, this paper argues that rather than coercive assimilation under a forced 'Filipino' identity construction, the Philippine government’s accommodation policies through the NCMF's cultivation of cultural sensitivity allow groups to access equitable progress and development of Muslim Filipino minorities. NCMF’s interventions enable vulnerable minorities to transition towards becoming stakeholders shaping an inclusive shared future. Institutionalizing Wasaṭiyya through the NCMF is crucial for the Philippines as it provides a culturally sensitive approach to Muslim minority integration, potentially mitigating historical tensions and fostering sustainable peace. Embedding Wasaṭiyya principles in responsive governance infrastructure, the NCMF plays an invaluable role in reconciling the Philippines' complex past tensions between state and minorities to effect sustainable conflict transformation through prudent accommodation.